2020
DOI: 10.1007/s11244-020-01356-2
|View full text |Cite
|
Sign up to set email alerts
|

Water Disinfection Using Chitosan Microbeads With N-, C-, C-N/TiO2 By Photocatalysis Under Visible Light

Abstract: Chitosan microbeads with C-doped TiO 2 , N-doped TiO 2 and C,N-codoped TiO 2 were prepared to obtain photocatalysts with higher photocatalytic efficiency, active under visible light and easy to removed from aqueous medium. TiO 2 powders were synthesized by the sol-gel method and modified using glucose and ammonium nitrate as source of C and N, respectively. Scanning electron microscope (SEM), X-ray diffraction (XRD), DRUV-Vis spectra and Raman techniques, were used to characterize the modified TiO 2 powders. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…N-doped TiO2 powder XRD results were found to be strongly dependent on the nitrogen precursor. In the case of ammonia (as in this study) [19], ammonium nitrate [20], and nitric acid [21] as nitrogen precursors, no visible changes in the TiO2 crystal structure were observed; i.e., the N-doped TiO2 crystalline phase was determined by the synthesis conditions (mainly the calcination temperature, which determines the share of anatase and rutile phases), as in the case of undoped TiO2. As a result, no significant differences between N-doped and undoped TiO2 can be seen in the XRD patterns.…”
Section: Catalysts Characterizationmentioning
confidence: 58%
“…N-doped TiO2 powder XRD results were found to be strongly dependent on the nitrogen precursor. In the case of ammonia (as in this study) [19], ammonium nitrate [20], and nitric acid [21] as nitrogen precursors, no visible changes in the TiO2 crystal structure were observed; i.e., the N-doped TiO2 crystalline phase was determined by the synthesis conditions (mainly the calcination temperature, which determines the share of anatase and rutile phases), as in the case of undoped TiO2. As a result, no significant differences between N-doped and undoped TiO2 can be seen in the XRD patterns.…”
Section: Catalysts Characterizationmentioning
confidence: 58%
“…This phenomenon is attributed to a well/poor dispersion of the different metallic ions on the surface of the TiO 2 [40]. Previous studies have shown that the photocatalytic efficiency of TiO 2 was improved by doping with different elements, since this process affects the particle size and the crystalline phase of the materials, achieving an adequate transfer of the photoexcited electron-hole pairs [53]. The modified TiO 2 samples show a slight increase in crystallite size due to metallic ions (presence of defects), which is directly related to the decrease in the band gap, that in turn, may improve their photocatalytic activity against organic pollutants [54,55].…”
Section: X-ray Diffractionmentioning
confidence: 99%